Unsteady Hybrid Nanofluid Flow On A Stagnation Point Of A Permeable Rigid Surface - Pop, Ioan; Waini, Iskandar; Ishak, Anuar (John Wiley and Sons Inc., 2021)
This study investigates the unsteady flow of Al2O3-Cu/water hybrid nanofluid on a stagnation point of a permeable rigid surface. The similarity equations are obtained using similarity variables and then solved using the bvp4c solver. The outcomes show that dual solutions exist for the negative unsteadiness and some mass flux parameters. Besides, the heat transfer rate is intensified with the hybrid nanoparticles. Moreover, the increasing of the mass flux parameter tends to increase the heat transfer rate and the skin friction on the surface. Also, the reduction of the skin friction coefficient is observed, and a higher heat transfer rate is achieved for smaller values of the unsteadiness parameter. Finally, by a temporal stability analysis, it is found that the first solution is stable and reliable as time evolves